Preparation of carboxymethyl cellulose based microgels for cell encapsulation - Y. Ke; G. S. Liu; J. H. Wang; W. Xue; C. Du; G. Wu (eXPRESS Polymer Letters, 2014)
Biocompatible and biodegradable carboxymethyl cellulose (CMC) has been modified with 4-hydroxybenzylamine (CMC-Ph) in order to prepare CMC-based microgels through the horseradish peroxidise/hydrogen peroxide enzymatic reaction. CMC-Ph was identified as a blend, and the amount of the grafted 4-hydroxybenzylamine per 100 units of CMC was between 17 and 23 according to the molecular weight of CMC. Through a special designed co-flowing microfluidic device, CMC-Ph microgels were prepared with the radius from 100 to 500 μm via adjusting the flow rates of the disperse phase and the continuous phase, respectively. The chondrocytic cell line ATDC5 was encapsulated in the CMC-Ph microgels. The cell-laden microgels were cultured for up to 40 days, illustrating the biocompatibility of CMC-Ph and the microfluidic approach through the enzymatic crosslinking reaction primarily. CMC-Ph showed a great promise to encapsulate the cells for further fabrication of the injectable scaffolds.